La emergencia de la ciudadanía juvenil. Resistencias, paradojas y tensiones en contextos urbanos contemporáneos (2016)
The purpose of this article is, rather than describe the practices and other expressions of citizenship, understanding the constructions thereon have become different juvenile stages of the city of Bogotá. The same is the result of a research process that was part of the macro project “construction of citizenship in different social scenarios” led by Pilot Colombia University in partnership with the Polytechnic Grancolombiano, and called for this case three organizations and youth groups belonging different scenarios between institutional and non-institutional. For the same discursive qualitative methods such as focus group and narrative social mapping, which allowed very clearly approaching its own categorical constructions of interest of the study, such as social practices, participation and empowerment processes and appropriation adopted young people in urban settings.